Efficacy and safety of the innovative monoclonal antibodies in adults with generalized myasthenia gravis: a Bayesian network analysis - Chen, Huiru; Qiu, Youjia; Yin, Ziqian; Wang, Zilan; Tang, Yanbing; Ni, Hanyu; Lu, Jiaye; Chen, Zhouqing; Kong, Yan; Wang, Zhong (Frontiers in Immunology, 2023)
Abstract Background: A series of clinical trials support the effectiveness of monoclonal antibodies for generalized myasthenia gravis (MG) compared to the placebo, but the priority among drugs remains unclear. Therefore, we conduct a frequentist network meta-analysis (NMA) to compare the relative effects of different drugs for generalized MG. Methods: PubMed, Embase, Cochrane Library, and clinicaltrials.gov were systematically searched for eligible studies up to 1 June 2023. The primary outcome was efficacy (Myasthenia Gravis Activities of Daily Living [MG-ADL] score and Quantitative Myasthenia Gravis [QMG] score) and safety (adverse events [AEs]). Mean difference (MD) and risk ratio (RR) with their 95% credible intervals (95%CrIs) were used to show the effect size of continuous and categorical variables, respectively. The quality of evidence was assessed using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach. Results: Thirteen studies involving 1167 individuals were identified for NMA. For efficacy outcomes, belimumab, efgartigimod, mezagitamab 600mg, and nipocalimab 60mg/kg were inferior to rozanolixzumab 7mg/kg (MD ranged from 2 to 3.69) and rozanolixzumab 10mg/kg (MD ranged from 2.04 to 3.72) in MG-ADL score, and rozanolixzumab had the highest rank probability (83%) according to the subjective surface under the curve ranking area (SUCRA). For QMG score, batoclimab 340mg (MD ranged from 4.32 to 8.52) and batoclimab 680mg (MD ranged from 4.11 to 9.31) were more effective than placebo and other monoclonal antibodies except for rozanolixzumab, with the highest SUCRA value (93% and 97% respectively). For safety outcomes, belimumab achieved the highest SUCRA value (89.8%) with significant statistical difference compared to rozanolixzumab 7mg/kg (RR 0.08, 95%CrI 0.01 to 0.94) and rozanolixzumab 10mg/kg (RR 0.08, 95%CrI 0.01 to 0.86). Conclusion: While all monoclonal antibodies were superior to the placebo, rozanolixzumab and batoclimab might be the most effective for generalized MG. However, rozanolixzumab was associated with higher incidence of AEs. Given the limitations inherent in indirect comparisons, further head-to-head and extensive observational studies are necessary to confirm our findings.